Attractiveness of constitutive and herbivore-induced sesquiterpene blends of maize to the parasitic wasp - Fontana, A.; Held, Matthias; Fantaye, C. A.; Turlings, Ted; Degenhardt, Jörg; Gershenzon, Jonathan (My University, 2011)
Plant volatile compounds induced by herbivore attack have been demonstrated to provide a signal to herbivore enemies such as parasitic wasps that use these volatiles to locate their hosts. However, in addition to herbivore-induced volatiles, plants often release volatiles constitutively. We assessed the interaction between herbivore-induced and constitutively released volatiles of maize in the attraction of the wasp Cotesia marginiventris that parasitizes herbivorous lepidopteran larvae feeding on maize. Experiments were carried out with olfactometers in which the sources of volatiles were transgenic Arabidopsis thaliana plants overexpressing maize sesquiterpene synthases that produce blends of herbivore-induced or constitutive compounds. We found that the constitutive volatiles of maize terpene synthase 8 (TPS8) were attractive to C. marginiventris, just like the herbivore-induced volatiles of TPS10 studied earlier. A mixture of both the TPS8 and TPS10 volatile blends, however, was more effective in parasitoid attraction, indicating that constitutively released sesquiterpenes enhance the attraction of those induced by herbivores. While C. marginiventris did not distinguish among the volatiles of TPS8, TPS10, nor those of another maize sesquiterpene synthase (TPS5), when these blends were combined, their attractiveness to the wasp appeared to increase with the complexity of the blend.
Keywords: Cotesia marginiventris; Arabidopsis thaliana; Zea mays; Spodoptera; littoralis; Sesquiterpenes; Volatile organic compounds (VOCs); Herbivore-induced volatiles; Constitutive volatiles; Plant defense; Parasitoid attraction; induced plant odors; volatile organic-compounds; campoletis-sonorensis; microplitis-croceipes; arabidopsis-thaliana; behavioral-responses; diaeretiella-rapae; indirect defense; natural enemies; predatory mite